Factors Driving the Use of Fintech M-Banking: A Survey of University Students in Palembang City - Agustina, Feny; Rachmat, Ryan Al (Jurnal Akuntansi, 2025)
This study aims to examine the influence of the Technology Acceptance Model (TAM) and Digital Financial Literacy (LKD) on the use of fintech mobile banking among students in Palembang City. The data was collected through an online questionnaire with 111 respondents and analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM). The results show that Perceived Usefulness (PU) and LKD have a positive and significant effect on the use of fintech mobile banking, while Perceived Ease of Use (PEU) does not have a significant influence. However, LKD significantly mediates the influence of PU and PEU on mobile banking adoption. Multigroup analysis also reveals no significant differences between male and female students in adopting this technology. This study highlights the importance of digital financial literacy as a key factor in promoting the adoption of digital banking services among students. Therefore, developing digital financial literacy programs is recommended to enhance students' understanding and ability to optimally utilize financial technology.